2020
DOI: 10.3390/e22060674
|View full text |Cite
|
Sign up to set email alerts
|

Natural Time Analysis of Global Navigation Satellite System Surface Deformation: The Case of the 2016 Kumamoto Earthquakes

Abstract: In order to have further evidence of the atmospheric oscillation channel of the lithosphere-atmosphere-ionosphere coupling (LAIC), we have studied criticality in global navigation satellite system (GNSS) surface deformation as a possible agent for exciting atmospheric gravity waves (AGWs) in the atmosphere and GNSS fluctuations in the frequency range of AGWs with the use of the natural time (NT) method. The target earthquake (EQ) is the 2016 Kumamoto EQ with its main shock on 15 April 2016 (M = 7.3, universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…It is also evident from Figures 7-10 that there is also example of post seismic AGW excitation. This could have several reasons starting from several aftershocks and many other meteorological phenomena [43] [59].…”
Section: Discussionmentioning
confidence: 99%
“…It is also evident from Figures 7-10 that there is also example of post seismic AGW excitation. This could have several reasons starting from several aftershocks and many other meteorological phenomena [43] [59].…”
Section: Discussionmentioning
confidence: 99%
“…Natural time was introduced [ 5 ] in 2001 as a general method to analyze time-series resulting from complex systems [ 7 ]. It has been applied to a variety of fields, such as condensed matter physics [ 22 , 23 , 24 ], geophysics [ 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], civil engineering [ 35 , 36 , 37 , 38 ], climatology [ 39 , 40 , 41 , 42 ], and biomedical engineering [ 43 , 44 ]. Within the concept of NTA, it has been shown that the variance of natural time may be considered as an order parameter for seismicity [ 3 , 45 , 46 , 47 , 48 , 49 ] as well as in acoustic emission before fracture [ 28 , 50 ] or in other self-organized critical phenomena such as ricepiles [ 51 ] and avalanches in the Olami–Feder–Christensen [ 52 ] earthquake model [ 53 ] or in the Burridge–Knopoff [ 54 ] train model [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the old days, when we proposed the AGW hypothesis, we were always criticized that there is no evidence of surface deformation before an EQ. Recently, there have been several important published papers on the pre-EQ surface deformation based on the GPS, seismic measurements [55,[98][99][100][101]. Chen et al (2020) [99] found clear fluctuations in the frequency range in the earth's surface deformation before large EQs, and suggested the presence of an AGW resonator in the lithosphere.…”
Section: Stratospheric Effectsmentioning
confidence: 99%
“…As is given in Hayakawa et al (2004) [32], the first is so-called chemical channel, in which emanation of radioactive radon and/or gases is considered to play the main player, leading to the modification of atmospheric conductivity and generation of electric field, thereby driving a variation in the ionospheric plasma density [7,28,35,[46][47][48][49]. The second is acoustic channel, in which atmospheric oscillations, including atmospheric gravity waves (AGWs) and acoustic wave, are excited by the precursory deformation of ground motion and/or gas emanation [8,33,[50][51][52][53], propagating upwards to the lower and upper ionosphere and leading to a perturbation in the ionosphere [54][55][56][57]. The third is electromagnetic channel [32], where electromagnetic waves generated in any frequency range propagate upwards into the ionosphere and magnetosphere, inducing the particle precipitation into the upper atmosphere due to wave-particle interactions in the magnetosphere (e.g., [58][59][60][61]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation